Design and Implementation an IoT-Based Electric Motor Temperature and Vibration Handling System - Aryo De Wibowo Muhammad Sidik; Anggy Pradiftha Junfithrana; Anang Suryana; Marina Artiyasa; Ilman Himawan Kusumah; Edwinanto (Universitas Nusa Putra, 2022)
Faults in three-phase electric motors often occur in power plants. Unfortunately, the disturbances are unpredictable and reduce unit performance. This paper presents an Internet of Things (IoT) based intrusion handling system for secure and economic data communication in industrial fields. The build system can monitor and control with FLM (First Line Maintenance). FLM is a minor corrective maintenance activity carried out while the unit operates with the provision of simple equipment. Device design and testing using the ESP8266 microcontroller module to obtain motor vibration, current, and temperature information for motor conditions and supported by the application as a user interface. The result is to prevent further damage to the electric motor by adding an external fan and a grease pump to cool the engine. This research contributes to improving the performance of the generator at PT. Indonesia Power UJP West Java II Palafruitratu is one of the steam power plants in West Java, Indonesia.